The association between frailty, care receipt and unmet need for care with the risk of hospital admissions - Maharani, Asri; Sinclair, David R.; Clegg, Andrew; Hanratty, Barbara; Nazroo, James; Tampubolon, Gindo; Todd, Chris; Wittenberg, Raphael; O’Neill, Terence W.; Matthews, Fiona E. (PLOS ONE, 2024)
Background Frailty is characterised by a decline in physical, cognitive, energy, and health reserves and is linked to greater functional dependency and higher social care utilisation. However, the relationship between receiving care, or receiving insufficient care among older people with different frailty status and the risk of unplanned admission to hospital for any cause, or the risk of falls and fractures remains unclear. Methods and findings This study used information from 7,656 adults aged 60 and older participating in the English Longitudinal Study of Ageing (ELSA) waves 6–8. Care status was assessed through received care and self-reported unmet care needs, while frailty was measured using a frailty index. Competing-risk regression analysis was used (with death as a potential competing risk), adjusted for demographic and socioeconomic confounders. Around a quarter of the participants received care, of which approximately 60% received low levels of care, while the rest had high levels of care. Older people who received low and high levels of care had a higher risk of unplanned admission independent of frailty status. Unmet need for care was not significantly associated with an increased risk of unplanned admission compared to those receiving no care. Older people in receipt of care had an increased risk of hospitalisation due to falls but not fractures, compared to those who received no care after adjustment for covariates, including frailty status. Conclusions Care receipt increases the risk of hospitalisation substantially, suggesting this is a group worthy of prevention intervention focus.